Four weeks of high cadence training alter brain cortical activity in cyclists - Ludyga, S.; Hottenrott, K.; Gronwald, T. (Journal of Sports Sciences, 2017)
Exercise at different cadences might serve as potential stimulus for functional adaptations of the brain, because cortical activation is sensitive to frequency of movement. Therefore, we investigated the effects of high (HCT) and low cadence training (LCT) on brain cortical activity during exercise as well as endurance performance.